Pengaruh Konseling Kelompok CBT Teknik Biblioterapi untuk Meningkatkan Kemampuan Manajemen Waktu - Purwaningsih, Dwi Afriani; Lianasari, Dewi (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
This research aims to examine the effect of CBT group counselingwith bibliotherapy techniques to improve students' time managementskills. The research was conducted on grade VII students of SMPNegeri 39 Purworejo T.A 2020/2021.This research is a type of pre-experimental research with theresearch design used is one group pretest-posttest design. Theresearch subjects were selected by purposive sampling. The samplestaken were 6 class VII students. The data collection method is doneby using a time management capability scale. The data analysistechnique used statistical parametric analysis with paired sample ttestwiththehelpofSPSS24forWindows. TheresultsofthisstudyindicatethattheCBTgroupcounselingwith bibliotherapy techniques have an effect on improving students' timemanagement skills, this is evidenced by the results of the pairedsample t-test with a probability of Sig. (2-tailed) 0.015 <0.05. Theresults also showed an increase in the average posttest score of14.33.